WHITE BOX TESTING PADA SISTEM PEMESANAN DESAIN SABLON BERBASIS WEB - Abdi Pandu Kusuma; Bayu Setiawan (Jurnal Teknika, 2018)
Ordering a screen printing design is built as a supporting tool to anticipate cheating buyers in ordering goods that  are  normally  done  through  the  marketplace.  By  using  this  system  the  user  must  enter  the  order  number obtained after the customer makes an order in the marketplace for verification if they want to make a design order. Admin can manage user access to order designs and manage the design queue properly. White box testing method is done to find out how the system works structurally, besides to find out things that might happen when the system is run. In the white box test on the user login page and the design orderi ng page, the system works well as evidenced from the testing phase as in Cyclomatic Complexity and Matrix produces a value of 2 for the user login page and 1 for the design message page.